Ethics in Social Research and Its Impact on Policy Implication, Planning and Development (Bangladesh Journal of Bioethics, 2020)
This paper is an attempt to discuss how ethics associated with social research in connection with the collection of authentic and reliable data, use of appropriate data process and impartial data analysis for preparing an acceptable research report. Ethics is closely related to moral integrity, and values associated with appropriate methods and techniques applied for collection of reliable and authentic information that ensure the trust worthy research findings. This paper is based on secondary data collected through reviewing the relevant literatures. This paper examine to what extent the research findings contribute to the knowledge of planners and policy makers in formulating the  appropriate policy and at the same time preparing effective as well as pragmatic  planning based on the quality of research findings and finally thus may affect on development.